Activity and mechanism of naringin in the treatment of post-infectious cough - Yinghan Chen; Dong Wang; Meng Song; Weiqi Pan; Wenda Guan; Zifeng Yang; Shan Zhong (BMC Pulmonary Medicine)
Abstract Objective To explore activity and mechanism of naringin in the treatment of PIC (Post-Infectious Cough) by virtue of network pharmacology and animal studies. Methods The targets associated with naringin were obtained from the SwissTargetPrediction and Super-PRED databases. Disease-related targets were collected from GeneCards and OMIM (Online Mendelian Inheritance in Man). Venny was utilized to identify the overlapping targets between naringin and the disease. PPI (Protein–Protein Interaction) networks for disease-related targets were constructed using STRING and Cytoscape 3.10.1. GO (Gene Ontology) functional annotation and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analyses were performed with Metascape. Molecular docking between key targets and naringin was conducted using AutoDock Vina. In the animal experiments, PIC models were established in guinea pigs via intranasal inoculation with A/PR/8 virus, and cough frequency was measured after citric acid-induced coughing. Morphological changes in lung tissue and airways were assessed using the HE (Hematoxylin–Eosin) staining method. The relative expression levels of IL-8 (Interleukin-8), IL-1β (Interleukin-1β), TNF-α (Tumor Necrosis Factor-Alpha), and NF-κB p65 (Nuclear Factor Kappa-B p65 Subunit) mRNA were analyzed by RT-qPCR (Reverse Transcription Quantitative Polymerase Chain Reaction). SOD (Superoxide Dismutase) activity in lung tissue was measured using a colorimetric assay. Results After screening, naringin may contribute to the treatment of post-infectious cough by targeting proteins expressed by core genes such as HSP90AA1 (HSP 90-Alpha), TLR4 (Toll-like Receptor 4), MTOR (Mechanistic Target of Rapamycin), HIF1A (Hypoxia-Inducible Factor Alpha), and NF-κB1 (Nuclear Factor Kappa-B Subunit 1). KEGG enrichment analysis revealed involvement in pathways including the HIF-1 (Hypoxia-Inducible Factor 1) signaling pathway and the PD-L1 (Programmed Death-Ligand 1) expression and PD-1 (Programmed Cell Death Protein 1) checkpoint pathway in cancer. Molecular docking results indicated that naringin exhibited strong binding affinity with HSP90AA1, TLR4, MTOR, HIF1A, NF-κB1, NOS3 (Nitric Oxide Synthase 3), and GRB2 (Growth Factor Receptor-Bound Protein 2). In animal experiments, compared to the normal group, guinea pigs in the model group exhibited a significantly higher number of coughs, pronounced lung tissue hyperplasia, and inflammatory cell infiltration. Additionally, the relative expression of IL-8, IL-1β, TNF-α, and NF-κB p65 mRNA was significantly increased, while lung tissue SOD activity was decreased. Treatment with naringin significantly reduced the number of coughs, attenuated pathological changes in lung tissue, lowered the lung index, decreased the relative expression of IL-8, IL-1β, TNF-α, and NF-κB p65 mRNA, and significantly increased SOD activity in lung tissue compared to the model group. Conclusion Naringin shows therapeutic potential to alleviate PIC symptoms in a guinea pig model through anti-inflammatory and antioxidant mechanisms.